2010 Annual Report Conference on Electrical Insulation and Dielectic Phenomena 2010
DOI: 10.1109/ceidp.2010.5724089
|View full text |Cite
|
Sign up to set email alerts
|

Use of electrospinning to disperse nanosilica into silicone rubber

Abstract: Nanomaterials have attracted considerable attention due to their unique physicochemical properties. However, agglomerations of nanofillers in nanocomposites have hindered the potential improvements to their properties. A novel technique of infusing nanosilica into silicone rubber with reduced agglomeration is reported in this paper. The technique involves electrospinning of silicone fibers, embedded with nanosilica, and incorporating the fibers into silicone rubber. Compared to high shear mechanical mixing, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…This technique is simple, cheap and scalable and has been used to e.g. disperse nanosilica in silicone rubber with good particle distribution and dispersion [15].…”
Section: Processingmentioning
confidence: 99%
“…This technique is simple, cheap and scalable and has been used to e.g. disperse nanosilica in silicone rubber with good particle distribution and dispersion [15].…”
Section: Processingmentioning
confidence: 99%
“…Apparently, the distribution of fiber diameter became wider at higher speed ratio, possibly because the higher concentration of SR in the electrospun solution further decreased the conductivity and viscosity of the electrospun solution. Bian et al also reported the difficulties in forming SR fiber due to its low conductivity and viscosity11 and only beads and droplets were obtained. Recently, Angammana and Jayaram reported a novel method for electrospinning insulating materials by using ion liquid with high electrical conductivity 12.…”
Section: Resultsmentioning
confidence: 99%
“…When the filler loading is changed from 3 wt% to 10 wt%, a more uniform dispersion of the nanofiller can be achieved using this technique than what can be obtained with the conventional high shear force mechanical mixing method [13][14].…”
Section: Sample Preparationmentioning
confidence: 99%
“…In our previous study work, a uniform dispersion of nanosilica in silicone rubber using an electrospinning technique was demonstrated. It was found that the effective dispersion of the nanofillers permitted greater amounts of nanosilica to be loadedinto the electrospun samples [13][14] than into the samples prepared through conventional mixing. This study represented a novel application of the use of electrospinning to disperse nanofillers since it used mainly electrical forces and the high shear force created by the polymer stretch during the electrospinning process to separate the filler agglomerations, which overcomes the specific limitations of conventional physical and chemical mixing methods.…”
Section: Introductionmentioning
confidence: 99%